Cryopreservation of Swamp Buffalo Semen in Skim Milk Yolk-based Diluent with Two Different Cryoprotectants - M. T. Herbowo; R. I. Arifiantini; N. W. K. Karja; R. G. Sianturi (Faculty of Animal Science, Bogor Agricultural University, 2019)
The successful of artificial insemination (AI) in buffalo is still low. The quality of frozen semen determines the successful of AI program. Glycerol is widely used for cryopreservation of buffalo semen with unsatisfactory results due to its toxicity and antifertility properties. This study aimed to investigate the effect of glycerol and dimethylformamide (DMF) concentrations in skim milk egg yolk (SMEY)–based diluent on the quality of frozen-thawed swamp buffalo bull semen. Fresh semen was divided into eight aliquots. Each aliquot was diluted in SMEY containing 4%, 5%, 6%, and 7% glycerol and 4%, 5%, 6%, and 7% DMF. Diluted semen was packed into mini straw (0.25 mL), equilibrated at 4 °C for 4 hours, frozen in liquid nitrogen vapor for 10 minutes, and stored at liquid nitrogen container. The straws were thawed after 24 hours at 37 °C for 30 seconds for evaluation. The results showed that the post thawed sperm motility and recovery rate in SMEY extender containing 7% glycerol and 5% DMF were higher than the other glycerol or DMF concentrations. Post thawed sperm viability and plasma membrane integrity in SMEY containing 4%-6% DMF did not differ significantly, however both values were higher than those in 7% DMF. Post thawed sperm viability and plasma membrane integrity did not differ between SMEY containing 6% and 7% glycerol. However, both values were higher than those in 4% and 5% glycerol. It is concluded that 7% glycerol or 5% DMF is considered to be the most suitable cryoprotective agent for swamp buffalo semen cryopreservation.The successful of artificial insemination (AI) in buffalo is still low. The quality of frozen semen determines the successful of AI program. Glycerol is widely used for cryopreservation of buffalo semen with unsatisfactory results due to its toxicity and antifertility properties. This study aimed to investigate the effect of glycerol and dimethylformamide (DMF) concentrations in skim milk egg yolk (SMEY)–based diluent on the quality of frozen-thawed swamp buffalo bull semen. Fresh semen was divided into eight aliquots. Each aliquot was diluted in SMEY containing 4%, 5%, 6%, and 7% glycerol and 4%, 5%, 6%, and 7% DMF. Diluted semen was packed into mini straw (0.25 mL), equilibrated at 4 °C for 4 hours, frozen in liquid nitrogen vapor for 10 minutes, and stored at liquid nitrogen container. The straws were thawed after 24 hours at 37 °C for 30 seconds for evaluation. The results showed that the post thawed sperm motility and recovery rate in SMEY extender containing 7% glycerol and 5% DMF were higher than the other glycerol or DMF concentrations. Post thawed sperm viability and plasma membrane integrity in SMEY containing 4%-6% DMF did not differ significantly, however both values were higher than those in 7% DMF. Post thawed sperm viability and plasma membrane integrity did not differ between SMEY containing 6% and 7% glycerol. However, both values were higher than those in 4% and 5% glycerol. It is concluded that 7% glycerol or 5% DMF is considered to be the most suitable cryoprotective agent for swamp buffalo semen cryopreservation.